Design method of combined cooling, heating, and power system coupled with cascaded latent heat thermal energy storage based on supply-demand energy-exergy matching. (15th September 2022) - Mo, Junrong; Dai, Xiaoye; Xu, Shuhan; Shi, Lin
Highlights: Energy and exergy loss of latent heat thermal energy storage (LHTES) is analysed. A phase-change temperature design method is proposed for cascaded LHTES system. The design operation is based on the principle of matching supply and demand. The CCHP system was coupled with cascaded LHTES for improved performance. Abstract: Thermal energy storage is an effective method to alleviate the energy mismatch between the combined cooling, heating, and power (CCHP) system and its users. This paper proposes a CCHP system coupled with cascaded latent heat thermal energy storage to develop a design method considering the supply–demand matchings of energy and exergy. Three forms of thermal energy storage systems are introduced for comparison—the traditional single-stage latent heat thermal energy storage, simple form cascaded latent heat thermal energy storage, and coupled form cascaded latent heat thermal energy storage systems—and the corresponding thermodynamic models are constructed. Based on supply–demand energy-exergy matching, the phase-change temperatures of the coupled form cascaded latent heat thermal energy storage system are optimised and the design-operation method of the power generation unit is presented. Then under different cooling-to-electricity and heating-to-electricity ratios, the performances of the three thermal energy storage systems and their corresponding CCHP systems are compared based on matching coefficient, exergy efficiency, and energy-saving rate. The results indicate that the coupled form cascaded latent heat thermal energy storage system has the best matching performance; the maximum matching coefficient and exergy efficiency are 0.9228 and 63.54%, respectively, whereas those of the single-stage latent heat thermal energy storage system are 0.2747 and 24.55%; the CCHP system coupled with coupled form cascaded latent heat thermal energy storage has the highest energy-saving rate in most cases. Further, the case study of a hospital in China shows that the energy-saving rate of the proposed system is 23.32% whereas that of the CCHP system coupled with single-stage latent heat thermal energy storage is 8.51%. Consequently, the proposed system and design method can help improve the matching relationship and system performance.